Update on rotavirus vaccine underperformance in low- to middle-income countries and next-generation vaccines - Benjamin Lee (Human Vaccines & Immunotherapeutics, 2021)
In the decade since oral rotavirus vaccines (ORV) were recommended by the World Health Organization for universal inclusion in all national immunization programs, significant yet incomplete progress has been made toward reducing the burden of rotavirus in low- to middle-income countries (LMIC). ORVs continue to demonstrate effectiveness and impact in LMIC, yet numerous factors hinder optimal performance and evaluation of these vaccines. This review will provide an update on ORV performance in LMIC, the increasing body of literature regarding factors that affect ORV response, and the status of newer and next-generation rotavirus vaccines as of early 2020. Fully closing the gap in rotavirus prevention between LMIC and high-income countries will likely require a multifaceted approach accounting for biological and methodological challenges and evaluation and roll-out of newer and next-generation vaccines.